Unusual brachiopod fauna from the Middle Triassic algal meadows of Mt. Svilaja (Outer Dinarides, Croatia). (27th November 2015) - Halamski, Adam T.; Bitner, Maria Aleksandra; Kaim, Andrzej; Kolar-Jurkovšek, Tea; Jurkovšek, Bogdan
Abstract: Ladinian deposits at Mt. Svilaja in Dalmatia (Outer Dinarides, Croatia) yielded an abundant brachiopod fauna of low diversity interpreted as a parautochthonous assemblage representing an ecosystem of dasycladacean submarine meadow. The fauna consists of four named species and one left in open nomenclature. The most common is the spiriferinide Flabellocyrtia flabellulum Chorowicz and Termier, 1975 (Spiriferinida) accounting for more than 70% of the material. The athyridide Cassianospira humboldtii (von Klipstein, 1845) is the only species known from elsewhere (Anisian of Southern Alps). The new species of Spiriferinida Thecocyrtella dagysii Halamski, Bitner, Kaim, Kolar-Jurkovšek, and Jurkovšek n. sp. differs from other representatives of the genus in having a deep ventral sulcus. Albasphe albertimagni Halamski, Bitner, Kaim, Kolar-Jurkovšek, and Jurkovšek n. gen. n. sp. is a new brachiopod that possesses a dorsal septum with an intra-septal cavity and dorsal submarginal ridges, both features in common with Aalenian Zellania Moore, 1855 from which it differs in lack of the ventral septum and of ventral submarginal ridges. They are interpreted as members of a sparsely recorded paedomorphic evolutionary line of terebratulides with secondarily lost loop, described formally herein as Gwyniidina Halamski and Bitner n. subordo and subdivided into newly emended Dispheniidae Grant, 1988 (Dispheniinae Grant, 1988 with the only genus Disphenia and Albasphinae Halamski and Bitner n. subfam. with Albasphe and Zellania ) and Gwyniidae MacKinnon, 2006 (including Recent Gwynia and Simpliciforma ). In contrast to previous interpretations, the trocholophe lophophore of Gwynia is interpreted herein as secondarily simplified.